Arsenic pollution - Häder, Donat-Peter (Springer International Publishing, 2021)
Arsenic is a frequent element on Earth and occurs on all continents and has been detected in over 70 countries. It is found in 10% of the global tube wells providing groundwater for millions of people. Since it has no odor, taste or color it is often not detected especially in developing countries where it causes major deleterious effects on the biota and human health. Chronic exposure to arsenic (especially trivalent As) causes skin problems, brain damage, lung and cardiovascular diseases as well as various cancers. It accumulates in plants and enters aquatic food webs. Arsenic can be detected by laboratory tests as well as field tests, but the latter are often not very reliable. Other means of detection are by several bioassays. There are several strategies of removal of arsenic from water for human consumption as well as industrial and agricultural use such as precipitation, reverse osmosis, ion exchange or adsorption. For developing countries, cheap filtration units have been developed and tested in the field.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Aquatic ecosystems; Arsenic; Detection; Human health; Quantification; Remediation